On the issue of the concept and socio-legal appointment of the regime of execution of preventive measures in the form of detention - Kyzdarbekova, B.Zh. (Bulletin of the Karaganda University “Law Series”, 2018)
In the article, an attempt is made to deepen the rationale for a fundamentally new understanding of the regime as an order and conditions for the implementation of preventive measures in the form of detention. The main approaches to the definition of the concept of «the regime of execution of preventive measures in the form of detention in custody» and its socio-legal appointment in the doctrine of criminally-executive law were identified and examined. The author substantiates the conclusion that the regime, or rather its requirements, must meet the goals of this preventive measure. The allocation of the educational regime to the detention regime is questioned. The author draws a line between the concepts of the regime of the place of detention and the regime of execution of the preventive measure in the form of detention. The latter applies exclusively to suspects and accused persons subject to this measure of criminal procedural coercion, while the regime of the place of detention extends not only to the said persons, but also to all categories of persons who are in these institutions, not excluding employees. In this regard, the concept of the regime of the place of detention is broader than the concept of the regime for the implementation of this preventive measure. Based on the analysis, the author's definition of the concept of «the regime of execution of preventive measures in the form of detention» is formulated, and the idea of the necessity of including this concept in the acting Law of the RK «On the order and conditions of detention of persons in special institutions that provide temporary isolation from society».